Optimal Strategy of Primary Frequency Regulation for Wind-Storage System Considering Adaptive Parameter Control. (1st March 2023) - Liu, Yang; Yang, Zhihao; Zhang, Zhenan; Sun, Xin; Wei, Wenrong; Miao, Shihong
Abstract: For the problem that the power system has different demands on the frequency response characteristics in different segments of dynamic frequency response, this paper proposes an optimal primary frequency regulation strategy for the wind-storage system considering adaptive parameter control. Firstly, the dynamic frequency response processes of the system under single, continuous disturbances are analyzed to obtain the frequency regulation demand of the system in different segments. Secondly, the frequency response model of the power system is established to obtain the transfer function of the system's primary frequency regulation. Finally, the adaptive parameter adjustment strategy of the wind-storage system is proposed, and the optimal primary regulation strategy of the wind-storage system is established. The result of the case study indicates that the proposed optimal primary frequency regulation strategy can effectively improve the performance of the power system in the dynamic frequency response process, especially when a continuous disturbance occurs.